A new method for predicting the ultimate shaft resistance of rock-socketed drilled shafts. Issue 2 (1st July 2019) - Xu, Jiang; Gong, Weiming; Gamage, Ranjith Pathegama; Zhang, Qi; Dai, Guoliang
Abstract : Data from 187 loading tests on rock-socketed shafts are used to develop a new relationship between the ultimate shaft resistance f su and unconfined compressive strength σ c of intact rock. The adhesion factor α q of the shaft resistance for different types of rock and the relationship between α q and the embedment ratio are discussed. Furthermore, because the shafts are socketed in the natural rock mass, as well as the aforementioned correlation with intact rock, three new relationships between f su and the unconfined compressive strength σ cm of the rock mass are proposed by considering the rock quality designation, which is related to discontinuity of the rock mass. Statistical methods are used to evaluate and verify the existing methods and newly proposed relationships. Results obtained using the new relationship based on σ c are found to be more accurate than those obtained using existing methods, and when the rock quality designation is available, results obtained using σ cm are closer to measured values than those based on σ c . The value of α q of the discussed rocks decreases with σ c . Mudstone and shale have relatively high values of α q with more dispersion, whereas α q values for gneiss, basalt and granite are small overall with less dispersion.